Functional maturation of human pluripotent stem cell derived cardiomyocytes in vitro – Correlation between contraction force and electrophysiology. (May 2015) - Ribeiro, Marcelo C.; Tertoolen, Leon G.; Guadix, Juan A.; Bellin, Milena; Kosmidis, Georgios; D'Aniello, Cristina; Monshouwer-Kloots, Jantine; Goumans, Marie-Jose; Wang, Yu-li; Feinberg, Adam W.; Mummery, Christine L.; Passier, Robert
Abstract: Cardiomyocytes from human pluripotent stem cells (hPSC-CM) have many potential applications in disease modelling and drug target discovery but their phenotypic similarity to early fetal stages of cardiac development limits their applicability. In this study we compared contraction stresses of hPSC-CM to 2nd trimester human fetal derived cardiomyocytes (hFetal-CM) by imaging displacement of fluorescent beads by single contracting hPSC-CM, aligned by microcontact-printing on polyacrylamide gels. hPSC-CM showed distinctly lower contraction stress than cardiomyocytes isolated from hFetal-CM. To improve maturation of hPSC-CM in vitro we made use of commercial media optimized for cardiomyocyte maturation, which promoted significantly higher contraction stress in hPSC-compared with hFetal-CM. Accordingly, other features of cardiomyocyte maturation were observed, most strikingly increased upstroke velocities and action potential amplitudes, lower resting membrane potentials, improved sarcomeric organization and alterations in cardiac-specific gene expression. Performing contraction force and electrophysiology measurements on individual cardiomyocytes revealed strong correlations between an increase in contraction force and a rise of the upstroke velocity and action potential amplitude and with a decrease in the resting membrane potential. We showed that under standard differentiation conditions hPSC-CM display lower contractile force than primary hFetal-CM and identified conditions under which a commercially available culture medium could induce molecular, morphological and functional maturation of hPSC-CM in vitro . These results are an important contribution for full implementation of hPSC-CM in cardiac disease modelling and drug discovery.